The Quran From The Perspective Of Acceptance And Commitment Therapy - Fatıma Firdevs Adam; Rukiye Gögen (Cumhuriyet İlahiyat Dergisi)

(untitled)
The purpose of this study is to discuss how the verses in the Holy Quran can be related to the flexible hexagon of Acceptance and Commitment Therapy. The issues discussed in the six steps of the Act are the issues emphasized in the Quran in order to ensure the happiness of people in this world and the hereafter. For believers, religion is the most important element that directs their lives. For this reason, when individuals who aim to continue their worldly life according to religious values encounter a problem or pain and want to get psychological support, both the client and the counselor may hesitate. Seeing the similar aspects of the Quran verses with ACT will make the work of the counselor and the client easier in the psychotherapy process. While applying this therapy to a believing client, the counselor will be able to benefit from the Holy Quran, which is the most important source according to his belief; The client will feel the pleasure that the counselor cares about his religious values. Therefore, the fact that psychological counseling techniques coincide with the messages given by the verses of the Quran will make it easier for Muslim clients to overcome the pain they experience, cope with difficulties, and most importantly, they will be able to go through the counseling process happily because it does not contradict their beliefs. For this reason, in the study, the components of the Act are explained in detail and its relationship with the verses in the Holy Quran is revealed.